Direct Printing of Reduced Graphene Oxide on Planar or Highly Curved Surfaces with High Resolutions Using Electrohydrodynamics. Issue 19 (21st January 2015) - An, Byeong Wan; Kim, Kukjoo; Kim, Mijung; Kim, So‐Yun; Hur, Seung‐Hyun; Park, Jang‐Ung
<x xml:space="preserve">Abstract</x> Electrohydrodynamic inkjet printing of reduced graphene oxide (RGO) is demonstrated to form complex geometric devices with high resolution (line width ≈ 5 mm). Both planar and highly curved surfaces (radius of curvature ≈ 60 mm) can be used as substrates. Demonstrations of counterfeit coin recognition using RGO patterns and all‐printed RGO transistors suggest substantial promise for applications in security and electronics.